Peningkatan Kemampuan Berhitung Siswa Kelas II Dengan Menggunakan Sempoa Aritmatika Di Sekolah Dasar - Hanifatul Rahmi; Juni Saputra; Welly Desriati; Fatmawati Fatmawati (Politeknik Negeri Cilacap, 2020)
The Community Service Program (PPM) which is carried out aims to improve the ability of Grade II students in Arithmetic using Sempoa media. Observation results at SDN 001 Rimba Sekampung Devotion to the mathematics learning community using this abacus media to improve students' numeracy skills. The material taught is Reading abacus beads, Teaching the sum of units, tens and hundreds with an abacus, Teaching subtraction units, tens and hundreds with an abacus This activity was carried out Monday through Tuesday, 28 and 29 January 2020, starting at 10:00 until 12.00 West Indonesian Time. This activity begins by providing a pre-test (pretest) to determine the ability to count the participants and a final test (posttest) at the end to determine the final ability after giving the material. The average value of the initial test is 6.5 and the final test is 8.9.